IDIOM SEKSUALITASUALITAS BAGI WANITA JAWA PEDESAAN - -, Suwardi; Widayat, Afendy (Diksi, 2006)
People in rural Javanese communities usually still faithfully make use of Javaneseidioms in expressing matters of sexuality. Javanese idiomatic expressions areamong the means of expressing sexuality which are traditional in nature. Suchexpressions are combinations of terms possessing semantic and cultural meanings.In them eastern ethics are strongly embedded. The use of such ethical idiomsenables rural Javanese parents to inseminate expressions of sexuality withrelatively more ease in feminine members of their society.The use of Javanese idioms is a manifestation of the expression of sexualitysymbolic in meaning. This is justified because the Javanese personality is revealedin the Javanese saying Wong Jawa iku nggoning semu., which means that theJavanese are where symbolism is. Some types of the idioms often used inexpressing feminine sexuality are (1) tembung entar, which is a figurativeexpression, (2) peribahasa, which is an expression describing someone's act, (3)saloka, which is an idiom in the form of an expression using the name of an objector animal, (4) pepindhan, which is a comparison of a sexual object to anotherobject, (5) panyandra, which is a description of a phenomenon of sexuality, and (6)piwulang, which is a teaching on sexuality. Of these, the first two types are themost often made use of. They are considered comparatively more easilyunderstood by those using them.Keywords: idiom, sexuality, women